Taṭbῑq Wasā’il al-ta’lῑm Educandy li Taḥsῑni Natā’ij at-Ta‘allum fῑ Mādda al-Lugah al-‘Arabiyah lῑ as-Saf al-Khāmis B fῑ al-Madrasah al-Ibtidā’iyyah Qurratu A‘yun: Penerapan Media Educandy Untuk Meningkatkan Hasil Belajar Dalam Materi Bahasa Arab Pada Kelas 5B MI Qurrota A’yun Yogyakarta - Raihana Nur Azizah; Ahmad Hidayatullah Zarkasyi; Astuti Sifa’urrohmah; Nur Izzah Humaira Hasyim (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2024)
Students in class 5B at MI Qurrota A’yun need help learning Arabic, which is considered problematic. The teaching method, limited to the teacher's guidebook, makes students feel less motivated and inactive during the learning process, negatively impacting their learning outcomes, which remain below the Minimum Completeness Criteria (KKM). Therefore, learning media that can improve students' interest and motivation is needed. One such media is Educandy, as its interactive form can attract students' attention and facilitate their understanding and memorization of vocabulary. Thus, this research aims to improve student's learning outcomes and enthusiasm in class 5B after applying Educandy media in Arabic language materials. The research method used in this study is Classroom Action Research (PTK), and the subjects are the students of class 5B at MI Qurrota A’yun. Data collected by the researcher from documentation, test results, observations, and interviews are analyzed through data reduction, data presentation, and conclusion drawing. This research shows that the application of educational learning media can improve students' learning outcomes in class 5B at MI Qurrota A’yun. The average score increased by 29% from 6.32 in the first round to 8.18 in the second round. Furthermore, the media also successfully increased the students' enthusiasm for learning, with an increase of 38% from 68% in the first round observation to 92% in the second round observation. Keywords: Learning Enthusiasm, Learning Outcomes, Teaching Aids (Educandy)